Genetic variants related to cell cycle and stability of telomere in patients with glioma - Calastri, Maria Clara Jessica; Hattori, Gabriela; Rodrigues, Nicolas Luz Toledo Ortega [UNESP]; Gregorio, Michele Lima; Brancati, Camila Ive Ferreira Oliveira; Zanovelo, Eliane Milharcix; Filho, José Roberto Lopes Ferraz; Neiva, Cassiano Merussi [UNESP]; Junior, Antonio Carlos Ponde Rodrigues; de Godoy, Moacir Fernandes; Lancellotti, Carmen Lucia Penteado; Tognola, Waldir Antonio; et al. (EpiSmart Science Vector, 2019)
Background: Glioma, most common primary malignant brain tumor in adults, is highly aggressive and associated with a poor prognosis. Evaluate the association of polymorphisms related of to the cell cycle, integrity and DNA repair with gliomas, as well as lifestyle habits, comorbidities, survival and response to treatment. Methods: Were studied 303 individuals distributed into: Study Group - 100 patients with gliomas, regardless of the degree of malignancy, and Control Group - 203 individuals without clinical signs of the disease. These polymorphisms were genotyped by TaqMan® SNP Genotyping Assay. Significance level was set at 5%. Results: Smoking, alcohol consumption, systemic arterial hypertension (SAH) and diabetes mellitus (DM) prevailed in patients, compared to controls (P=0.0088, P=0.0001, P=0.0001, P=0.0011, respectively). In the logistic regression analysis, alcohol consumption and SAH were identified as independent risk factors for gliomas (P=0.0001, P=0.0027, respectively). Patients with low-grade gliomas showed survival in one year (92.0±6.8%), compared to patients with high-grade gliomas (24.0±5.3; P=0.011). Conclusion: Polymorphisms involved in cell cycle, telomere protection and stability and DNA repair are not associated with gliomas. On the other hand, alcohol consumption and SAH stand out as independent risk factors for the disease. Low-grade gliomas, response to treatment and the combination of chemotherapy with Temozolomide and radiation therapy show increased survival of patients.
Keywords: Astrocytoma; Glioblastoma; Magnetic resonance spectroscopy; Polymorphism